2020
DOI: 10.1074/jbc.ra120.013015
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the antigenicity and immunogenicity of monomeric forms of hepatitis C virus E2 for use as a preventive vaccine

Abstract: The E2 glycoprotein of hepatitis C virus (HCV) is the major target of broadly neutralizing antibodies (bNAbs) that are critical for the efficacy of a prophylactic HCV vaccine. We previously showed that a cell culture–derived, disulfide-linked high-molecular-weight (HMW) form of the E2 receptor–binding domain lacking three variable regions, Δ123-HMW, elicits broad neutralizing activity against the seven major genotypes of HCV. A limitation to the use of this antigen is that it is produced only at low yields and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…Most importantly, higher antigen valency improves B cell receptor activation and increases complement system activation [ 71 ]. Importantly, our results confirm other studies that reported that a higher oligomeric state of E2, either as aggregate [ 62 , 65 ] or when presented on nanoparticles [ 72 , 73 , 74 ], enhances the immune response. Furthermore, a recent study showed that aggregated forms of E2, including a variant containing less cysteine residues, induce higher quality Abs in guinea pigs [ 65 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most importantly, higher antigen valency improves B cell receptor activation and increases complement system activation [ 71 ]. Importantly, our results confirm other studies that reported that a higher oligomeric state of E2, either as aggregate [ 62 , 65 ] or when presented on nanoparticles [ 72 , 73 , 74 ], enhances the immune response. Furthermore, a recent study showed that aggregated forms of E2, including a variant containing less cysteine residues, induce higher quality Abs in guinea pigs [ 65 ].…”
Section: Discussionsupporting
confidence: 91%
“…Later, crystal structures of a more complete E2 confirmed the existence of these three disulfide bonds, but also showed additional disulfide bonds that were not observed before [ 39 ]. We found that E2.C8A interacted equally well with monoclonal conformational antibodies as conventional E2 monomers and even better than E2 aggregates, which corresponds to the findings reported by a recent study on another recombinant E2 containing less cysteines [ 65 ].…”
Section: Discussionsupporting
confidence: 90%
“…Based on sequence analysis, primarily of genotype 1a, synthetic consensus sequences of E2 have been reported, but have not consistently improved immunogenicity [ 103 , 114 ]. HVR1 has been removed in many E2 core designs [ 77 , 101 , 104 , 115 ], as it can interfere with and enable evasion of bnAb responses [ 116 , 117 ]. In one case, HVR1 was found to determine sensitivity to heterologous neutralization by sera from goats immunized with an E1E2 vaccine candidate, in part through differential binding with co-receptor SR-BI [ 118 ].…”
Section: Design Approachesmentioning
confidence: 99%
“…Along with other variable regions, HVR1 was removed in an E2 core design that maintained binding to CD81 and formed an apparent homodimer [ 119 , 120 ]. A high-molecular-weight form of this E2 core design showed promising immunogenicity in guinea pigs [ 121 ], and has been further optimized through mutation of cysteine residues [ 104 ]. However, removing HVR1 alone does not appear to improve the immunogenicity of vaccine designs [ 115 , 122 ].…”
Section: Design Approachesmentioning
confidence: 99%
“…However, these treatments are linked to several drawbacks, such as high costs, drug resistance, or lack of protection against recurrence [ 24 ]. A variety of vaccine candidates are also in the development phase, with some having progressed to human clinical trials, including those based on synthetic peptides, recombinant proteins (core protein subunits and envelope proteins), viral vectors (virosome) and DNA (plasmid) [ 25 , 26 , 27 , 28 , 29 , 30 ]. Peptide and DNA-based vaccine candidates are currently being tested in murine models [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%